The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1111/j.1442-9993.1990.tb01527.x
|View full text |Cite
|
Sign up to set email alerts
|

Woody overstorey impact on herbaceous understorey in Eucalyptus spp. communities in central Queensland

Abstract: Native pasture yield and species composition within naturally occurring Eucalyptus communities of central Queensland were studied. Within a site, herbaceous yield decreased as tree basal area increased with the greatest relative decrease at sites with low pasture production potential. Mitscherlich regressions between herbaceous yield and tree basal area Y = A + B*e−kx) accounted for >80% of the observed variation at all sites. The absolute value of ‘k’ was greatest for those sites that had the lowest yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
34
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 18 publications
9
34
1
Order By: Relevance
“…In the woodlands of east-central Queensland, the increase in pasture yield upon clearing 10 has been demonstrated in earlier studies by Burrows, (1993), Burrows et al, (1999), and 11 Scanlan and Burrows, (1990), and was also evident in the present study. The present 12 research furthermore demonstrated that more of such benefits exist over the initial years of 13 clearing not over a longer term (>30 years).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In the woodlands of east-central Queensland, the increase in pasture yield upon clearing 10 has been demonstrated in earlier studies by Burrows, (1993), Burrows et al, (1999), and 11 Scanlan and Burrows, (1990), and was also evident in the present study. The present 12 research furthermore demonstrated that more of such benefits exist over the initial years of 13 clearing not over a longer term (>30 years).…”
supporting
confidence: 86%
“…Most studies to date (Scanlan and Burrows, 1990;Burrows, 1993;Burrows et al, 1999) 17 have highlighted the production gains from clearing, but these were limited to <10 years of 18 age of cleared pastures (Scanlan, 2002). Indeed, the initial gain in pasture production with 19 clearing is the only attractive phase for the landholders to clear land for pastures.…”
Section: Introductionmentioning
confidence: 99%
“…Generally the cleared land is sown to exotic productive grass species such as Cenchrus ciliaris L. that have higher root : shoot and root length : root biomass ratios than the original woody vegetation (Wilson 1998) and are associated with efficient capture of soil nutrients released upon clearing (Converys 1999). The increase in pasture production with clearing has been demonstrated in previous studies by Burrows et al (1990), Scanlan and Burrows (1990), and Burrows (2002).…”
Section: Introductionsupporting
confidence: 69%
“…The benefits of clearing could have been overstated in earlier studies conducted over a short-term (<10 years) (e.g. Scanlan and Burrows 1990;Scanlan 1991;Burrows 1993) because the long-term ecological effects were not considered. The present study questions the sustainability of pasture production in cleared pastures and emphasises the need to assess the benefits or otherwise of clearing over a longer term when and if pasture production may stabilise, and to quantify loss if any, of ecosystem function.…”
Section: Introductionmentioning
confidence: 99%
“…As the tree canopies developed, there was also a reduction in grass dry weight in the control plots over time and a reduction in standing grass biomass in these plots between 2008 and 2010. Such reductions in grass biomass with increasing tree canopy are widely reported (Jameson 1967;Walker et al 1986;Scanlan and Burrows 1990) and are important for decreasing biomass of standing fine fuels at ground layer in plantations, allowing forest managers to conduct prescribed burns with reduced risk of tree scorch and associated losses in growth rate. In the current study, the inter-row and row herbicide treatments significantly reduced scorch height at the time of the first prescribed burn despite the effectiveness of herbicide treatments being less obvious at this time.…”
Section: Discussionmentioning
confidence: 99%